DEVELOPING AUDIO MEDIA FOR TEACHING LISTENING - Puspita Sari, Hesty; Dini Sintia, Ayunda (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
This research was aimed to develop the investigation of English audio media for teaching listening to the seventh grade students. In this case, the product is an audio media, students’ book and the teacher’s book.The researcher applied Research and Development (R & D) design. In this research the potential problem and solution were obtained by analyzing the policy study, doing the observation, the interview, and the questionnaire. The result of finding potential problem and solution is that the listening practice is very rare to do and the teachers do not use the audio media yet.The result of the design and development showed that the Audio Media for Teaching Listening was valid, the average of the three material validators is 93% and the three media validators is 84%. The result of product trial showed that the model was effective. The research was carried out in VII A class of SMP N 2 Sutojayan, Blitar.The class consisted of 32 students involved in the need analysis and try out using one group pre and post test experimental design method. The result of pre- test (57.13) while the post test was(83.06). the result shows the increase of the students’ result. In paired samplet- test, t- count was -21.351 with sig 0.050. The implementation of validation and try out was in the final product, all steps of learning and exercise was based onTask Based Language Teaching (TBLT) approach that had three steps namelyPre- Task, Whilst- Task, and Post- Task. The Audio Media supported with the teacher’s book and students’ book.The product gave a significant effect to the students’ listening skill. It was valid and could be used as the media in teaching and learning process.The “Active Listening” Audio Media enhanced the students’ listening skill.